Nanocrystal - Masuda, Yoshitake (IntechOpen, 2011)
We focused on cutting-edge science and technology of Nanocrystals in this book. "Nanocrystal" is expected to lead to the creation of new materials with revolutionary properties and functions. It will open up fresh possibilities for the solution to the environmental problems and energy problems. We wish that this book contributes to bequeath a beautiful environment and valuable resources to subsequent generations.